An International Continence Society (ICS) report on the terminology for adult neurogenic lower urinary tract dysfunction (ANLUTD). Issue 3 (17th November 2017) - Gajewski, Jerzy B.; Schurch, Brigitte; Hamid, Rizwan; Averbeck, Márcio; Sakakibara, Ryuji; Agrò, Enrico F.; Dickinson, Tamara; Payne, Christopher K.; Drake, Marcus J.; Haylen, Bernie T.
Abstract : Introduction: The terminology for adult neurogenic lower urinary tract dysfunction (ANLUTD) should be defined and organized in a clinically based consensus Report. Methods: This Report has been created by a Working Group under the auspices and guidelines of the International Continence Society (ICS) Standardization Steering Committee (SSC) assisted at intervals by external referees. All relevant definitions for ANLUTD were updated on the basis of research over the last 14 years. An extensive process of 18 rounds of internal and external review was involved to exhaustively examine each definition, with decision‐making by collective opinion (consensus). Results: A Terminology Report for ANLUTD, encompassing 97 definitions (42 NEW and 8 CHANGED, has been developed. It is clinically based with the most common diagnoses defined. Clarity and user‐friendliness have been key aims to make it interpretable by practitioners and trainees in all the different groups involved not only in lower urinary tract dysfunction but additionally in many other medical specialties. Conclusion: A consensus‐based Terminology Report for ANLUTD has been produced to aid clinical practice and research.